CaO/CaCO₃ thermochemical energy storage performance of MgO/ZnO co-doped CaO honeycomb in cycles - Zhang, Youhao (2023)
The calcium-based honeycomb used in thermochemical energy storage (TCES) is promising for industrial applications, but its energy storage performance needs to be further improved. In this work, a novel MgO/ZnO co-doped calcium-based honeycomb for thermochemical energy storage was fabricated by extrusion molding method. The CaO/CaCO3 TCES performance of the MgO/ZnO co-doped CaO honeycomb was tested. ZnO and MgO show a synergistic impact on the CaO/CaCO3 TCES performance of the calcium-based honeycomb. The CaO honeycomb doped with MgO and ZnO exhibits the highest energy storage capacity with the mass ratio of CaO:MgO:ZnO of 100:10:3. After 25 cycles, the effective conversion and energy storage density of MgO/ZnO co-doped CaO honeycomb are 1.33 times those of the unmodified CaO honeycomb, respectively. MgO as the support improves the sintering resistance of the CaO honeycomb. ZnO strengthens the support effect of MgO for CaO and further improves the cyclic stability of the MgO doped CaO honeycomb in the multiple CaO/CaCO3 cycles. In addition, ZnO enhances the basicity and increases oxygen vacancies of the CaO honeycomb, which promotes energy storage. Moreover, MgO/ZnO co-doped CaO honeycomb exhibits much higher mechanical properties. The crushing strength of MgO/ZnO co-doped CaO honeycomb is 0.8 MPa after 20 cycles, which is 25.0 % higher than that of unmodified CaO honeycomb. The density functional theory calculation indicates that the movement of the CaO cluster is limited effectively by the Cac-Os bonds strengthened by ZnO and the Oc-Mgs bonds. Therefore, MgO/ZnO co-doped CaO honeycomb is a potential material for thermochemical energy storage.